(untitled) (Actual Problems of Psychology in Educational Institutions, 2022)
The article provides an analysis of trends in environmental education and training as elements of sustainable development strategies. The authors defines the key place of the ecological component of advanced education for sustainable development in the educational process, the ways of implementation of ecology basic knowledge in the education and upbringing of students are outlined.